INTESTINAL MALAKOPLAKIA IN A CHILD WITH RARE PRESENTATION - YADAV JK (International Journal of Pharma and Bio Sciences, 2015)
Malakoplakia of the intestine is a rare chronic inflammatory disorder, usually affecting colon and rectum. It is commonly seen in adults. Only few cases have been reported in children. I am presenting a rare case of malakoplakia of large intestine in eight year old boy who presented with multiple polyps in the colon.